(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Phonetic expressive means are integral to both literary and spoken discourse, providing aesthetic, emotional, and structural depth to texts. This thesis explores the nature of phonetic stylistic devices, emphasizing alliteration, onomatopoeia, rhyme, and rhythm. These devices, grounded in linguistic and poetic theory, shape the auditory and interpretative qualities of communication. The research draws on insights from scholars such as Roman Jakobson, I.R. Galperin, and Geoffrey Leech to illustrate how sound patterns contribute to meaning and artistry.